Effect of hydroalcoholic neem (Azadirachta indica) extract and oil on the fungus Fusarium oxysporum f. sp. vasinfectum and in the induced resistance of okra to fusariosis (Research, Society and Development, 2021)
The objective of this work was to verify the effect of hydroalcoholic extract and neem oil on mycelial growth, sporulation, germination, and conidia adhesion of the fungus F. oxysporum f. sp. vasinfectum. Also, to evaluate the effect of the extract and oil mentioned in the induction of resistance in treated okra trees and, later, inoculated with the fungus, through the activity of antioxidant enzymes related to plant defense processes. The results showed that both the extract and the neem oil were efficient in inhibiting mycelial growth and sporulation of the fungus. In addition, there was inhibition of germination and fixation of conidia produced in the presence of the products. Neem extract and oil reduced the severity of the disease in okra, as measured by the disease’s infection rate. In addition, significant increases in the enzymes guaiacol-peroxidase, polyphenoloxidase, superoxide dismutase and catalase were observed in the okra treated with the products, these increases being directly proportional to the increases in the concentrations used. Thus, both the extract and the neem oil have direct effects on the development of the fungus F. oxysporum f. sp. vasinfectum and induce resistance in okra from the formation of reactive oxygen species (ROS).